2015
DOI: 10.1159/000376550
|View full text |Cite
|
Sign up to set email alerts
|

High Impact of Histopathological Remission for Prognosis after Perioperative Chemotherapy with ECF and ECF-Like Regimens for Gastric and Gastroesophageal Adenocarcinoma

Abstract: Background: Perioperative chemotherapy with epirubicin, cisplatin and 5-fluorouracil (5-FU) (ECF)-like regimens is the European standard for patients with adenocarcinoma of the gastroesophageal junction (GEJ) or gastric body (GaCa) stage UICC II/III (staged according to the Union for International Cancer Control). However, limited data exist on the histopathological response and relevance of prognosis for patients homogeneously treated with ECF(-like) therapies. Methods: All patients with GEJ/GaCa treated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several problems impelled us to carry out similar clinical research on GC. Firstly, GC patients achieving pCR after NAC is uncommon in clinical practice, the pCR rate were respectively 13.0%, 10.0% and 16.0% by using the ECF(like) (38), DCF (39), and FLOT (6) regimen (6). Next, clinical response seems to correlate poorly with pathology in preoperative staging of gastric adenocarcinoma after NAC, Thirdly, pathological response has a higher validity than radiography (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several problems impelled us to carry out similar clinical research on GC. Firstly, GC patients achieving pCR after NAC is uncommon in clinical practice, the pCR rate were respectively 13.0%, 10.0% and 16.0% by using the ECF(like) (38), DCF (39), and FLOT (6) regimen (6). Next, clinical response seems to correlate poorly with pathology in preoperative staging of gastric adenocarcinoma after NAC, Thirdly, pathological response has a higher validity than radiography (36).…”
Section: Discussionmentioning
confidence: 99%
“…The final cohort resulted from me different cohorts (Figure 1). The first cohort ("ECF-cohort", n = 49) was based on pts who receiv treatment between 2005 and 2008 as part of the ECF study [15]. This w study performed at our institution, in which pts with upper-GI tumou The first cohort ("ECF-cohort", n = 49) was based on pts who received their curative treatment between 2005 and 2008 as part of the ECF study [15].…”
Section: Methodsmentioning
confidence: 99%
“…The first cohort ("ECF-cohort", n = 49) was based on pts who receiv treatment between 2005 and 2008 as part of the ECF study [15]. This w study performed at our institution, in which pts with upper-GI tumou The first cohort ("ECF-cohort", n = 49) was based on pts who received their curative treatment between 2005 and 2008 as part of the ECF study [15]. This was a monocentric study performed at our institution, in which pts with upper-GI tumours received ECF (epirubicin/cisplatin/5-FU) in the context of multimodal therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Published data indicated that patients who pathologically respond to neoadjuvant chemotherapy have a better prognosis after surgery than patients who do not respond to chemotherapy (Bichev et al 2015). Because some patients with gastric cancer are insensitive to chemotherapeutics, the evaluative criteria of iconography to predict the effect of neoadjuvant chemotherapy are very important.…”
Section: Introductionmentioning
confidence: 99%